The contribution of caregiver psychosocial factors to distress associated with behavioural and psychological symptoms in dementia. (18th February 2016) - Feast, Alexandra; Orrell, Martin; Russell, Ian; Charlesworth, Georgina; Moniz‐Cook, Esme
Abstract : Objective: The objective of the study is to examine caregiver factors as predictors of BPSD‐related distress and their potential mechanisms. Method: Informal caregivers of people with dementia ( n = 157) recruited from 28 community mental health teams in six NHS Trusts across England completed questionnaires regarding psychosocial factors (relationship quality, competence, guilt, health‐related quality of life in the caregiver and person with dementia, reactivity to behavioural and psychological symptoms in dementia [BPSD] and burden) and frequency of BPSD. Analyses of BPSD‐related distress include hierarchical multiple regression, mediation, moderation and path analysis. Results: Caregiver psychosocial factors explained 56% of the variance in BPSD‐related distress. After controlling for these factors, frequency of BPSD was not a significant predictor of BPSD‐related distress. Caregiver reactivity to BPSD, burden, competence and relationship quality directly influenced BPSD‐related distress. Guilt influenced distress indirectly via competence, burden and reactivity to BPSD. The final model accounted for 41% of the variance in BPSD‐related distress and achieved a good fit to the data (χ 2 = 23.920, df = 19, p = 0.199). Conclusions: Caregiver psychosocial factors including sense of competence, guilt, burden and reactivity to BPSD contribute to BPSD‐related distress. Tailored interventions for managing behaviour problems in family settings could focus on these factors associated with BPSD‐related distress to minimise distress in families. Copyright © 2016 John Wiley & Sons, Ltd.